Phage-Based Control of Listeria innocua in the Food Industry: A Strategy for Preventing Listeria monocytogenes Persistence in Biofilms - Anna Zawiasa; Marcin Schmidt; Agnieszka Olejnik-Schmidt (Viruses)
Listeria innocua, though considered non-pathogenic, frequently coexists with Listeria monocytogenes in industrial environments, aiding its survival in biofilms. These biofilms pose a significant challenge in food processing facilities, as they protect bacteria from disinfectants and facilitate their spread. The aim of this review was to identify bacteriophages as a promising method for eliminating Listeria biofilms from the food industry. Lytic bacteriophages show great potential in combating Listeria biofilms. Commercially available products, such as PhageGuard Listex™ (P100) (Micreos Food Safety, Wageningen, The Netherlands), effectively reduce both L. monocytogenes and L. innocua in food products and on production surfaces. Additionally, phage-derived enzymes, such as endolysins, can degrade biofilms, eliminating bacteria without compromising food quality. The following article highlights that although bacteriophages present a promising biocontrol method, further research is necessary to assess their long-term effectiveness, particularly regarding bacterial resistance. To maximize efficacy, a combination of strategies such as phage cocktails and disinfectants is recommended to enhance biofilm eradication and minimize food contamination risks.